A Model for Strengthening Learning Achievement Through an Approach to the Use of Social Media and Learning Motivation - Sijabat, Rauly; Indriyani, Kristin Anita; Purwantini, Sri; Sulistiyowati, Elly; Djari, Janny Adriani (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: Student learning achievement is the output of an educational institution. Achievement of learning achievement is determined by external and internal factors of students. Therefore, the learning achievement of each student varies. This phenomenon prompted this research to examine the influence of the use of social media as an external factor in learning achievement and learning motivation as an internal factor in learning achievement on learning achievement using empirical data. Design/methodology/approach: The research was conducted on 146 cadets of the Semarang Maritime Science Polytechnic (PIP) which was carried out through interviews using a questionnaire. The data obtained was then analyzed using the Structural Equation Modeling (SEM) approach. Findings: From the results of this research it can be proven that social media is statistically proven to have a significant positive effect on learning motivation and learning achievement and learning motivation is statistically proven to have a significant positive effect on learning achievement Research limitations/implications: This research has not categorized internal and external factors. Practical implications: Based on the results of this research, to improve student learning achievement, it can be done through two approaches. First, learning achievement can be improved by increasing students' learning motivation. The second approach to improving learning achievement is through the use or utilization of social media. Originality/value: This research focuses on vocational education. Paper type: Research Paper